Activity of Fengycin and Iturin A Isolated From Bacillus subtilis Z-14 on Gaeumannomyces graminis Var. tritici and Soil Microbial Diversity - Xiao, Jiawen; Guo, Xiaojun; Qiao, Xinlei; Zhang, Xuechao; Chen, Xiaomeng; Zhang, Dongdong (Frontiers in Microbiology, 2021)
Bacillus subtilis Z-14 can inhibit phytopathogenic fungi, and is used as a biocontrol agent for wheat take-all disease. The present study used the soil-borne fungus Gaeumannomyces graminis var. tritici (Ggt), which causes wheat take-all disease, and the soil microbial community as indicators, and investigated the antifungal effects of fengycin and iturin A purified from strain Z-14 using high performance liquid chromatography and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry, respectively. The results showed that fengycin destroyed the internal structure of Ggt cells by digesting the cytoplasm and organelles, forming vacuoles, and inducing hyphal shrinkage and distortion. Iturin A induced cell wall disappearance, membrane degeneration, intracellular material shrinkage, and hyphal fragmentation. A biocontrol test demonstrated a 100% control effect on wheat take-all when wheat seedlings were treated with fengycin at 100 µg/ml or iturin A at 500 µg/ml. Iturin A and fengycin both reduced the relative abundance of Aspergillus and Gibberella. At the genus level, iturin A reduced the relative abundance of Mortierella and Myrothecium, while fengycin reduced that of Fusarium. Only fengycin treatment for 7 days had a significant effect on soil bacterial diversity.